The Influence of Education and Training on Civil Servant Performance Mediated by Competence - Gani, Ilham; Lewaherilla, Novalien C.; Pentury, Gerrit M. (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
Education and training programs for civil servants (ASN) have been intensified, yet bureaucratic performance, particularly in mining supervision, remains suboptimal. This study aims to examine the effect of education and training on ASN performance with competence as a mediating variable. Using a quantitative approach with PLS-SEM analysis on 41 respondents from the Inspector of Mines Office in North Maluku Province. This study found that education does not have a significant effect on either the competence or performance of civil servants. In contrast, training has a significant effect on competence but not directly on performance. Competence was proven to have a significant effect on performance and mediates the relationship between training and performance, but does not mediate the relationship between education and performance. These findings indicate that improvements in civil servant performance in the mineral and coal subsector are more strongly influenced by competencies gained through training rather than formal education, highlighting the strategic role of competency-based training programs in enhancing performance.